Temperature-responsive self-contraction nanofiber/hydrogel composite dressing facilitates the healing of diabetic-infected wounds - Yakun Huang; Meilin Song; Xianchao Li; Yanran Du; Zhongfei Gao; Yu-Qing Zhao; Chengbo Li; Huanhuan Yan; Xiumei Mo; Chunhua Wang; Guige Hou; Xianrui Xie (Materials Today Bio, 2024)
Bacterial infections and long-term inflammation cause serious secondary damage to chronic diabetic wounds and hinder the wound healing processes. Currently, multifunctional hydrogels have shown promising effects in chronic wound repair. However, traditional hydrogels only keep the wound moist and protect it from bacterial infection, and cannot provide mechanical force to contract the wound edges to achieve facilitated wound closure. Here, an asymmetric composite dressing was created by combining biaxially oriented nanofibers and hydrogel, inspired by the double-layer structure of the traditional Chinese medicinal plaster patch, for managing chronic wounds. Specifically, electrospun Poly-(lactic acid-co-trimethylene carbonate) (PLATMC) nanofibers and methacrylate gelatin (GelMa) hydrogel loaded with Epinecidin-1@chitosan (Epi-1@CS) nanoparticles are assembled as the temperature-responsive self-contracting nanofiber/hydrogel (TSNH) composite dressing. The substrate layer of PLATMC nanofibers combines topological morphology with material properties to drive wound closure through temperature-triggered contraction force. The functional layer of GelMa hydrogel is loaded with Epi-1@CS nanoparticles that combine satisfactory cytocompatibility, and antioxidant, anti-inflammatory, and antibacterial properties. Strikingly, in vivo, the TSNH dressing could regulate the diabetic wound microenvironment, thereby promoting collagen deposition, facilitating angiogenesis, and reducing the inflammatory response, which promotes the rapid healing of chronic wounds. This study highlights the potential of synergizing mechanical and biochemical signals in enhancing chronic wound treatment. Overall, this TSNH composite dressing is provided as a reliable approach to solving the long-standing problem of chronically infected wound healing.